2017
DOI: 10.1016/j.jchromb.2017.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a UHPLC-ESI-MS/MS method for the simultaneous quantification of mammal lysophosphatidylcholines and lysophosphatidylethanolamines in serum

Abstract: Recent investigations based on non-targeted metabolomics have proposed lysophospholipids (Lyso-PLs) as biomarkers of different diseases. In particular, lysophosphatidylcholines (Lyso-PCs) and lysophosphatidylethanolamines (Lyso-PEs) have been associated with serious lipid pathologies. Methods to determine the different molecular species in a biological sample and to quantify even less abundant species are required for the evaluation of the Lyso-PL pattern as a novel comprehensive biomarker of dyslipidemia. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Based on the exhaustive study of the fragmentation data, we concluded that both patterns represented Lyso-PL species. In addition, all these Lyso-PLs identified were molecular species containing the acyl chain in sn1 -position, which generally is the most common circulating isomer for these metabolites 38 . When collision energies of 10 V were applied in the positive ionization mode, several daughter ions were generated: a) the loss of the phosphorylethanolamine head group ([M + H] + −141), b) the loss of water ([M + H] + −18), c) the ion corresponding to the ethanolamine ([M + H] + = 62) and its fragment, d) the ethylamine ([M] + = 44), e) the phosphocholine ([M – H + 2 H] + = 184), and f) choline ions ([M + H] + = 104).…”
Section: Resultsmentioning
confidence: 98%
“…Based on the exhaustive study of the fragmentation data, we concluded that both patterns represented Lyso-PL species. In addition, all these Lyso-PLs identified were molecular species containing the acyl chain in sn1 -position, which generally is the most common circulating isomer for these metabolites 38 . When collision energies of 10 V were applied in the positive ionization mode, several daughter ions were generated: a) the loss of the phosphorylethanolamine head group ([M + H] + −141), b) the loss of water ([M + H] + −18), c) the ion corresponding to the ethanolamine ([M + H] + = 62) and its fragment, d) the ethylamine ([M] + = 44), e) the phosphocholine ([M – H + 2 H] + = 184), and f) choline ions ([M + H] + = 104).…”
Section: Resultsmentioning
confidence: 98%
“…A separate analysis nevertheless identified strongly elevated LPC in the liver of MCD diet and high fat diet fed mice [52]. This suggests that hepatic LPC levels were modified by diet, genetics and / or housing conditions [53] but were not mandatory for NASH pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For all the identified LysoPC in this study, LysoPC(14:0) and LysoPC(15:0) were upregulated in post‐treatment patients compared to pre‐treatment patients after adjusting clinical medication therapies. LysoPC, a series of abundant polar lipids, can participate in peroxidation and biosynthetic dysfunction of membrane phospholipids . LysoPC are also components of oxidized low‐density lipoprotein and regulate multiple biological processes, such as apoptosis control .…”
Section: Discussionmentioning
confidence: 99%